ANK1 and DnaK-TPR, Two Tetratricopeptide Repeat-Containing Proteins Primarily Expressed in Toxoplasma Bradyzoites, Do Not Contribute to Bradyzoite Differentiation - Yang, Jichao; Zhang, Lihong; Diao, Huiyan; Xia, Ningbo; Zhou, Yanqin; Zhao, Junlong; Shen, Bang (Frontiers in Microbiology, 2017)
Toxoplasma gondii is an important zoonotic pathogen infecting one third of the world population and numerous animals. A key factor to its wide distribution is the ability to interconvert between fast replicating tachyzoites and slowly growing bradyzoites, and to establish lifelong chronic infection in intermediate hosts. Although it is well accepted that stage conversion plays key roles in the pathogenesis and transmission of the parasite, little is known about the molecular mechanisms behind it. Using existing gene expression data from TOXODB and published work, we looked for proteins with novel functional domains and whose expression is up-regulated in the bradyzoite stage, hoping to find molecules that have critical roles in regulating stage conversion and bradyzoite formation. In this study we characterized two such proteins ANK1 and DnaK-TPR, both of which are primarily expressed in bradyzoites and contain novel motifs to mediate protein-protein interactions. Through CRISPR/CAS9 directed gene editing technology, both genes were individually knocked out in type 1 strain TgHB2 and type 2 strain ME49. Disruption of neither of these two genes affected the growth or replication of tachyzoites in vitro, consistent with their minimal expression at this stage. However, mutants lacking ANK1 or DnaK-TPR displayed modest virulence attenuation during mice infection. Surprisingly, inactivation of neither ANK1 nor DnaK-TPR seemed to have a significant impact on bradyzoite differentiation in vitro or cyst formation in vivo. These results suggest that ANK1 and DnaK-TPR probably do not directly contribute to bradyzoite differentiation, but likely affect other aspects of bradyzoite biology.